2015
DOI: 10.1016/j.mric.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance–Guided Passive Catheter Tracking for Endovascular Therapy

Abstract: Synopsis The use of MR guidance for endovascular intervention is appealing due to its lack of ionizing radiation, high-contrast visualization of vessel walls and adjacent soft tissues, multiplanar capabilities, and potential to incorporate functional information such as flow, fluid dynamics, perfusion, or cardiac motion. Concurrent advances in the design of “real-time” MR fluoroscopy pulse sequences and the development of MR compatible endovascular devices have facilitated progress from initial in vitro and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…The active needle prototypes were well visualized even when using relatively thick 8 mm slices (Figure 9). The in vivo visualization performance was found acceptable and comparable to previously reviewed iMRI devices 12,17,27 by the interventional cardiologists and MRI technologists in our group when using a validated acquisition strategy. Hence, we believe that clinical translation of the needle prototype is feasible.…”
Section: Discussionsupporting
confidence: 66%
“…The active needle prototypes were well visualized even when using relatively thick 8 mm slices (Figure 9). The in vivo visualization performance was found acceptable and comparable to previously reviewed iMRI devices 12,17,27 by the interventional cardiologists and MRI technologists in our group when using a validated acquisition strategy. Hence, we believe that clinical translation of the needle prototype is feasible.…”
Section: Discussionsupporting
confidence: 66%
“…An MR-certified guidewire could be useful for most of these catheterization procedures. The availability of certified equipment has long been a major bottleneck in the iCMR community (10,26 (27). Knight et al showed that CMR-right heart catheterization can be incorporated into clinical practice for testing of pulmonary hypertension (24).…”
Section: Discussionmentioning
confidence: 99%
“…In order to visualise the previously described guidewires, passive negative markers are commonly employed. In the negative contrast approach, the incorporated materials or added markers make guidewires visible by introducing localised magnetic field inhomogeneities which lead to the dephasing of adjacent proton spins and a local signal void (susceptibility artefact) on an MR image [136,137]. The common method adopted by research groups and guidewire manufacturers involves the gluing or adhering (super)paramagnetic iron oxide microparticles embedded in curable resin at different (discrete) points along the length of the guidewire to provide better MR visibility.…”
Section: Guidewires and Selective Cathetersmentioning
confidence: 99%
“…An image is considered T 1 -weighted when the signal acquisition parameters are chosen to reflect the variations in T 1 (same applies to T 2 -weighted images). Passive markers can be further classified into negative contrast, positive contrast, and non-proton multispectral contrast [136].…”
Section: Mr Visibilitymentioning
confidence: 99%
See 1 more Smart Citation